Adherence Improvement of Five Moments Hand Hygiene with Increasing Motivation of Nurses - Menik Kustriyani; Ivana Probo Kaeksi; Tamrin Tamrin (Universitas Muhammadiyah Semarang, 2018)
Joint Commission International ( JCI ) required the achievement of 100% five moment hand hygiene for the nurses who have provided care to patients. The adherence of five moments hand hygiene has been done to reduce the incidence of nosocomial infections. The adherence of five moments hand hygiene has been determined by inside and outside factors, and one of the inside factors is the motivation. The research is a qualitative research with cross sectional approach. The number of sample is 153 nurses with the proportionate random sampling technique at the Public Hospital of Loekmono Hadi Kudus. The research instruments used the questionaire and observation sheet. The research showed the result of Rank Spearman test p value = 0,000 with r value = 0.296, positive correlation means that the higher the nurse motivation, the higher the nurse aderence of five moment hand hygiene.